Knowledge, perceptions, and clinical experiences on molar incisor hypomineralization among dental care providers in Hong Kong - Gianina Camille Sicangco Gamboa (BMC Oral Health, 2018)
Abstract Background Molar incisor hypomineralization (MIH) is an alarming problem with considerable challenges in management. This study aimed to evaluate and compare the knowledge, perceptions, and clinical experiences of molar incisor hypomineralization (MIH) between general dental practitioners (GDPs) and paediatric dentists (PDs) in Hong Kong. Methods A cross-sectional survey of 557 randomly selected GDPs (approximately 25% of all registered dentists) and all registered PDs (n = 31) were invited. They were asked to complete a 4-section questionnaire adapted and modified from a study by Gambetta-Tessini and co-workers on sociodemographic profiles, knowledge, experience, and perceptions regarding MIH. Data were analyzed with chi-square, Fisher’s exact, and multiple factor ANCOVA tests. Results The overall response rate was 43.37% (255/588). Majority (74.1%) of the respondents encountered MIH in their practices. A significantly higher mean knowledge score (46.33 ± 7.1) was observed among PDs than GDPs (43.09 ± 7.0) (P < 0.01) and among PDs who are 40 years old or younger (P < 0.001). Differences in treatment of MIH were also observed between PDs and GDPs (P < 0.05). Paediatric dentists were more confident in diagnosing and treating MIH (P < 0.001). Most respondents (87.8%) expressed a need for continuing education on MIH. Conclusion Continuing education on MIH is needed to assure that the highest quality of evidence-based care is given to patients with MIH. Dissemination of latest best evidence on MIH, especially to GDPs, will assure that the condition is accurately diagnosed and well managed.